Nghiên cứu môi tương quan giữa cấu trúc electron và khả năng ức chế ăn mòn kim loại của một số hợp chất 2-hiđroxy-4-metylaxetophenon benzoyl hiđrazoyl hiđrazon - Tân, Vũ Minh; Nhiêu, Phạm Văn; Minh Phương, Vũ Thị (Vietnam Journal of Chemistry, 2014)
Some 2-hydroxy-4-methylacetophenone benzoyl hydrazone compounds have been studied by the inhibition of copper corrosion in 3M nitric acid solution. The structure of some 2-hydroxy-4- methylacetophenone benzoyl hydrazone compounds was calculated by using the AM1 method of the quantum chemical program HyperChem 7.0. Results of the above calculation are coordinated with inhibitor efficiency (P) that is determined by experiment and both are applied to Statgraphics 4.1 software to carry out linear regression.